PELATIHAN PENYUSUNAN LAPORAN KEUANGAN SEDERHANA PADA UMKM RUFATA: Training in Preparing Simple Financial Reports for Rufata MSMES - Hartanti, Rina; Sipayung, Emma Saur Nauli; Tajib, Erny (ASOSIASI IDEBAHASA KEPRI, 2024)
The important role of MSMEs in the history of reducing unemployment rates during the economic crisis in Indonesia and as a booster for economic recovery after the Covid-19 pandemic cannot be separated from the creativity and hard work of MSME entrepreneurs in maintaining the sustainability of their businesses. The sustainability of MSME businesses will be maintained if MSME entrepreneurs not only carry out various innovative efforts to sell their business products or services but must also be able to manage the financial results of their business by increasing their knowledge and skills in preparing financial reports for all economic transactions of their business. Likewise, Rufata MSME entrepreneurs really need training from teachers or lecturers. The Bachelor of Accounting Study Program, Faculty of Economics and Business, Trisakti University collaborates with the Rufata MSME Coordinator, Cikokol Village, Pancoran District, South Jakarta, held a Community Service (PKM) program with the title: